Preparation method and application of CeO2 / NiS heterostructure catalyst
By synthesizing CeO2 precursors on nickel foam and vulcanizing to form CeO2/NiS heterostructure catalysts, the problems of high cost of noble metal catalysts and insufficient activity of NiS in alkaline environments are solved, and excellent hydrogen evolution, oxygen evolution and full water removal performance in electrolytic water reaction are achieved.
Patent Information
- Application Number
- CN202211000006.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-19
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-08-19
AI Technical Summary
In the prior art, the high cost and scarcity of precious metal catalysts limit the widespread application of electrolyzed water to prepare hydrogen, and NiS is insufficient in the alkaline environment, making it difficult to show great advantages in the hydrogen evolution and oxygen evolution reactions at the same time.
CeO2 precursor was synthesized on nickel foam by hydrothermal method, and CeO2/NF was obtained by annealing, followed by annealing and sulfurization in a nitrogen atmosphere using thiourea as the sulfur source to form a CeO2/NiS heterostructure catalyst, which was applied to the electrolytic water reaction under an alkaline environment.
The excellent HER, OER and full water-removing properties of CeO2/NiS catalyst in alkaline environments were achieved, the overpotential showed a lower value at an appropriate current density, the full water-removing properties showed a higher battery voltage, and the life and stability of the catalyst were improved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrocatalyst preparation and application, and specifically relates to the preparation and application of a CeO2 / NiS heterostructure catalyst. Technical Background
[0002] Against the backdrop of the increasing depletion of global resources, finding an environmentally friendly and renewable energy source can greatly alleviate the energy crisis. Among them, hydrogen has great potential to become a substitute for future energy consumption because its combustion products are green and pollution-free and have high energy density. It is worth noting that high-quality hydrogen can be produced by electrolysis of water. The water electrolysis reaction can be divided into two half reactions: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), but the efficiency of water electrolysis to produce hydrogen is limited by the slow kinetics of hydrogen evolution / oxygen evolution. Currently, precious metal Pt, Ru and Ir-based catalysts are the most effective water electrolysis catalysts, but their high cost and scarcity greatly limit their widespread application. Therefore, finding a non-precious metal-based catalyst that is suitable for both HER and OER will help the development of water electrolysis to produce hydrogen.
[0003] Among them, transition metal sulfides contain abundant active sites and have certain activity in electrocatalytic hydrogen evolution and oxygen evolution reactions. NiS has good metallicity and excellent conductivity due to its unique Ni-Ni bond, making NiS a non-precious metal-based catalyst with great potential for electrocatalytic water splitting. However, most of the current water electrolysis reactions occur in alkaline environments. In such harsh environments, the activity and stability of NiS will be affected to a certain extent. Reasonable design of heterostructures can not only improve the activity of NiS but also greatly improve the life of the catalyst. CeO2 has two different transition oxidation states Ce 3+ and Ce 4+ , and has excellent electronic conductivity, which helps promote charge transfer and improve energy conversion efficiency. In the prior art, there are "CeO2 modified Ni3S2 nanosheets for efficient electrocatalytic oxygen evolution" and "CN201910034437.X A method for preparing an in-situ synthesized transition metal oxide-nickel-based sulfide composite material". Most of the nickel-sulfur cerium dioxide composites prepared by these methods only study hydrogen evolution or oxygen evolution half-reactions, and their application in the complete water splitting reaction is still blank. And in electrocatalytic oxygen evolution, 20mA cm -2 The overpotential is 264mV, and the hydrogen evolution performance is also over -100mV. It is difficult to have great advantages in both hydrogen and oxygen evolution performances and have a very low water electrolysis starting voltage. Summary of the invention
[0004] In order to solve the problems in the background technology, the purpose of the present invention is to provide a CeO2 / NiS heterostructure catalyst and a preparation method thereof. When the CeO2 precursor is loaded by a hydrothermal method, part of the Ni element on the nickel foam will be doped into the CeO2 nanotubes, which is beneficial to promote the formation of the CeO2 / NiS heterojunction in the sulfidation process, and the heterostructured CeO2 / NiS catalyst is used in the electrolysis of water to prepare hydrogen in an alkaline environment, and has excellent HER, OER and full water splitting performance.
[0005] The technical solution of the present invention is as follows: the present invention provides a CeO2 / NiS heterostructure catalyst, and the preparation method of the catalyst is as follows: firstly, a CeO2 precursor is synthesized on nickel foam by a hydrothermal method, then CeO2 / NF is obtained by annealing in a tubular furnace in a nitrogen atmosphere, and finally, thiourea is used as a sulfur source, and CeO2 / NF is annealed in a tubular furnace in a nitrogen atmosphere to sulfurize CeO2 / NF into a CeO2 / NiS heterostructure catalyst.
[0006] The specific process is:
[0007] (1) The nickel foam was first ultrasonically treated with a 1M hydrochloric acid solution for 10 min to clean the oxide on the surface of the material, and then ultrasonically treated with an acetone solution for 10 min to clean the grease on the surface of the material, and then ultrasonically treated with ethanol and ultrapure water for 20 min each to clean the residual hydrochloric acid and acetone on the surface of the material.
[0008] (2) Dissolve a certain amount of cerium nitrate hexahydrate and urea in deionized water, wait until the solution is evenly mixed to obtain a mixed solution, transfer the mixed solution and nickel foam to a high-pressure reactor lined with polytetrafluoroethylene, place it in an oven at 120°C for hydrothermal reaction for 12 hours, and after the reaction is completed, take out the reactants, wash them with deionized water, and then vacuum dry them to obtain a catalyst that is a CeO2 / NF precursor.
[0009] The molar ratio of hexahydrated cerium nitrate to urea is 1:2-5, and the ratio of foamed nickel to hexahydrated cerium nitrate is 9 cm 2 :1mmol~4mmol.
[0010] As a preferred embodiment, the molar ratio of cerium nitrate hexahydrate to urea is 2:5, and the ratio of nickel foam to cerium nitrate hexahydrate is 9 cm 2 :2mmol.
[0011] If the concentration of cerium nitrate hexahydrate is too low, it will not be loaded on the nickel foam during the hydrothermal process, and the performance of the obtained catalyst is similar to that of nickel foam. If the concentration of cerium nitrate hexahydrate is too high, the loading amount will be too high, which will cause the nickel foam substrate to be unable to fully contact with the sulfurized gas when preparing the CeO2 / NiS heterostructure catalyst, thereby affecting the synthesis of the material.
[0012] (3) The CeO2 / NF precursor is annealed in a tubular furnace in a nitrogen atmosphere for 2 hours to obtain a catalyst CeO2 / NF, wherein the annealing temperature is 300°C to 500°C and the heating rate is 1°C / min.
[0013] Preferably, the annealing temperature is 400°C.
[0014] (4) CeO2 / NF and thiourea (sulfur source) were annealed in a tubular furnace in a nitrogen atmosphere for 2 h. Thiourea as a sulfur source was placed upstream of the tubular furnace to facilitate more thorough sulfurization of CeO2 / NF. The final catalyst obtained was a CeO2 / NiS heterostructure catalyst.
[0015] The annealing temperature was 300℃~500℃, the heating rate was 1℃ / min, and the ratio of thiourea and CeO2 / NF was 1g:1cm 2 .
[0016] Preferably, the annealing temperature is 400°C.
[0017] Among them, the purpose of using two annealings is to oxidize the CeO2 / NF precursor into CeO2 / NF material in the first annealing. Low temperature will affect the crystallinity of CeO2 on nickel foam, which is not conducive to the formation of CeO2 and NiS heterostructure in the later stage. Too high temperature will affect the performance of nickel foam substrate, causing nickel foam to become brittle, thus affecting the stability of the material. The purpose of the second annealing is to sulfurize CeO2 / NF into CeO2 / NiS heterostructure. If the CeO2 / NF precursor is directly subjected to 400°C sulfurization annealing without undergoing the first annealing, part of the CeO2 precursor will fail to be converted into CeO2, which will affect the formation of CeO2 / NiS heterostructure.
[0018] The present invention synthesizes a CeO2 precursor on nickel foam by a hydrothermal method, then obtains CeO2 / NF by annealing in a tubular furnace in a nitrogen atmosphere, and finally uses thiourea as a sulfur source and anneals the CeO2 / NF in a tubular furnace in a nitrogen atmosphere to sulfurize the CeO2 / NF into a CeO2 / NiS heterostructure catalyst. The present invention obtains a CeO2 / NiS heterostructure catalyst with optimal water electrolysis performance by optimizing the loading ratio of CeO2 on nickel foam and different annealing conditions, and finally applies the catalyst to hydrogen evolution, oxygen evolution and complete water electrolysis in an alkaline environment.
[0019] CeO2 / NiS heterogeneous structure catalyst is used in the electrocatalytic hydrogen evolution and oxygen evolution performance test method. A three-electrode system is used, the working electrode is CeO2 / NiS electrode, the counter electrode is a graphite rod electrode, the reference electrode is a Hg / HgO electrode, and the electrolyte is 1 mol / L KOH solution.
[0020] The CeO2 / NiS heterostructure catalyst was used in the electrocatalytic water splitting performance test method. A dual-electrode system was used. Both the working electrode and the counter electrode were CeO2 / NiS electrodes, and the electrolyte was 1 mol / L KOH solution.
[0021] The technical effects achieved by the present invention are:
[0022] (1) The CeO2 / NiS heterostructure catalyst provided by the present invention prepares a CeO2 and NiS heterostructure with good interface synergy, and the synthesis method is simple and the synthesis process is green and pollution-free.
[0023] (2) The CeO2 / NiS heterostructure catalyst provided by the present invention is a tubular nanowire structure, which can make the heterostructure and the electrolyte fully contact, thereby promoting the reaction.
[0024] (3) The CeO2 / NiS heterostructure catalyst provided by the present invention has excellent HER, OER and overall water splitting performance in alkaline electrolyte. The HER performance is -10mA / cm 2 The overpotential of -46 mV was shown at a current density of 10 mA / cm 2 The overpotential is 80 mV at a current density of 10 mA / cm 2 The battery voltage was 1.36 V at a current density of . BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The XRD patterns of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are shown in FIG.
[0026] Figure 2 This is the SEM image of Example 1.
[0027] Figure 3 1 is a hydrogen evolution polarization curve diagram of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0028] Figure 4 1 is an oxygen evolution polarization curve diagram of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0029] Figure 5 1 is a graph showing the Tafel slope curves of hydrogen evolution of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0030] Figure 6 The oxygen evolution Tafel slope curves of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in FIG.
[0031] Figure 7 1 is a hydrogen evolution polarization curve diagram of Example 1, Example 2 and Example 3.
[0032] Figure 8 It is the oxygen evolution polarization curve diagram of Example 1, Example 2 and Example 3.
[0033] Fig. 9 This is the full water decomposition performance diagram of Example 1.
[0034] Fig.10 This is the hydrogen evolution stability of Example 1.
[0035] Fig.11 This is the oxygen evolution stability of Example 1.
[0036] Fig.12 This is the complete water stability of Example 1.
[0037] Fig.13 The XPS spectra of Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0038] The present invention further illustrates the technical features of the present invention with the following examples, but the protection scope of the present invention is not limited to the following embodiments.
[0039] Example 1
[0040] Preparation of 1.1 mol / L KOH solution
[0041] Dissolve 5.62 g KOH in 50 mL ultrapure water. After the KOH solution is completely dissolved and cooled, dilute to volume in a 100 mL volumetric flask.
[0042] 2. Preparation of Nickel Foam
[0043] A piece of nickel foam (NF, 3.0 cm×3.0 cm) was immersed in 1 M hydrochloric acid solution for 10 min of ultrasonic treatment, and the surface was treated with acetone solution for 10 min of ultrasonic treatment, followed by ethanol and ultrapure water for 20 min, respectively.
[0044] 3. Preparation of CeO2 / NF
[0045] 2 mmol of cerium nitrate hexahydrate was dissolved in 40 mL of deionized water and ultrasonicated for 10 min to completely dissolve it. Then 5 mmol of urea was added and ultrasonicated for 20 min to completely dissolve it. Then a 9 cm 2The nickel foam and the mixed solution were simultaneously transferred to an autoclave lined with polytetrafluoroethylene, and placed in an oven at 120°C for hydrothermal reaction for 12 hours. After the reaction was completed, the reactants were taken out, washed with deionized water, and then vacuum dried to obtain a catalyst, which was a CeO2 / NF precursor. Subsequently, the CeO2 / NF precursor was transferred to a tubular furnace in a nitrogen atmosphere, heated to 400°C at a heating rate of 1°C / min, and then annealed at 400°C for 2 hours. After the reaction was completed, the catalyst obtained was CeO2 / NF.
[0046] 4. Preparation of CeO2 / NiS
[0047] The area is 1cm 2 The CeO2 / NF electrode and 1g thiourea were simultaneously transferred to a tubular furnace in a nitrogen atmosphere. The thiourea was placed upstream of the CeO2 / NF electrode and the temperature was raised to 400°C at a heating rate of 1°C / min. Then, the mixture was annealed at 400°C for 2h. After the reaction, the catalyst obtained was a CeO2 / NiS heterostructure catalyst.
[0048] application
[0049] 1. Activation treatment of electrocatalyst
[0050] (1) The electrochemical hydrogen evolution reaction (HER) and the electrochemical oxygen evolution reaction (OER) use a three-electrode system with a working electrode area of 1 cm 2 CeO2 / NiS heterostructure catalyst, the counter electrode is a graphite rod electrode, the reference electrode is a Hg / HgO electrode, and the electrolyte is 1 mol / L KOH;
[0051] (2) The electrochemical water splitting reaction uses a two-electrode system, with both the working electrode and the counter electrode having an area of 1 cm 2 CeO2 / NiS heterostructure catalyst, the electrolyte is 1mol / L KOH;
[0052] (3) Cyclic voltammetry (CV) activation: Jiangsu Donghua DH7000 electrochemical workstation was used, and the CV program was adopted. The HER test range was 0-0.8 V vs. RHE, the scan rate was 100 mV / s, and the cycle was 20 cycles. The electrode reached a stable state. The OER test range was 1-1.8 V vs. RHE, the scan rate was 100 mV / s, and the cycle was 20 cycles. The electrode reached a stable state. The complete water splitting test range was 1-1.8 V, the scan rate was 100 mV / s, and the cycle was 20 cycles. The electrode reached a stable state.
[0053] 2. Linear sweep voltammetry (LSV) test
[0054] After activation, the program was switched to linear sweep voltammetry with a HER test interval of 0 to 0.8 V vs. RHE and a scan rate of 5 mV / s. The electrocatalyst was at -10 mA / cm 2 The overpotential of the electrocatalyst prepared in Example 1 was -46 mV. The OER test range was 1-1.8 V vs. RHE, the scan rate was 5 mV / s, and the electrocatalyst was at 10 mA / cm 2 The overpotential of the electrocatalyst prepared in Example 1 is 80 mV. The test interval for complete water splitting is 1-1.8 V, the sweep rate is 5 mV / s, and the electrocatalyst is at 10 mA / cm 2 When , the voltage of the electrocatalyst cell prepared in Example 1 is 1.36V.
[0055] 3. Stability test
[0056] After activation, the chronopotentiometry was used, with HER set to -10 mA, OER set to 10 mA, and water splitting set to 10 mA. The time was set to 54,000 s.
[0057] from Figure 1 It can be seen from the XRD that the CeO2 / NiS heterogeneous structure catalyst prepared in Example 1 has only two diffraction peaks of CeO2 and NiS, indicating that the CeO2 / NiS heterogeneous structure catalyst was successfully prepared. Figure 2 The SEM of CeO2 / NiS heterostructure shows the tubular nanowire structure. Fig.13 It can be seen from the XPS fine spectrum of Ni element that compared with NiS, the Ni of CeO2 / NiS heterostructure catalyst is 3+ 2p 3 / 2 The orbital shifted by 0.5 eV toward higher binding energy, indicating that the electrons were transferred from Ni to CeO2, indicating the successful preparation of the CeO2 / NiS heterostructure catalyst.
[0058] Example 2
[0059] Compared with Example 1, the difference is that in the preparation process, the annealing temperature in the fourth step of preparing CeO2 / NiS is changed to 300°C.
[0060] The application method is the same as in Example 1, and the HER performance is -10 mA / cm 2 The overpotential of -120 mV was shown at a current density of 10 mA / cm 2 The overpotential was 105 mV at a current density of 1.3 %.
[0061] Example 3
[0062] Compared with Example 1, the difference is that in the preparation process, in the fourth step of preparing CeO2 / NiS, the annealing temperature is changed to 500°C.
[0063] The application method is the same as in Example 1, and the HER performance is -10 mA / cm 2 The overpotential of -89 mV was shown at a current density of 10 mA / cm 2 The overpotential was 106 mV at a current density of 1.
[0064] Example 4
[0065] Compared with Example 1, the difference is that in the preparation process, in the third step of preparing CeO2 / NF, the cerium nitrate hexahydrate is changed to 1 mmol.
[0066] The application method is the same as in Example 1, and the HER performance is -10 mA / cm 2 The overpotential of -210 mV was shown at a current density of 10 mA / cm 2 It exhibits an overpotential of 476 mV at a current density of .
[0067] Example 5
[0068] Compared with Example 1, the difference is that in the preparation process, in the third step of preparing CeO2 / NF, the hexahydrate cerium nitrate is changed to 4 mmol.
[0069] The application method is the same as in Example 1, and the HER performance is -10 mA / cm 2 The overpotential of -76 mV was shown at a current density of 10 mA / cm 2 The overpotential was 94 mV at a current density of 1.3 %.
[0070] Comparative Example 1
[0071] Compared with Example 1, the difference is that CeO2 is not loaded on the nickel foam by a hydrothermal method, and the obtained electrode is a NiS electrode.
[0072] The application method is the same as in Example 1, and the HER performance is -10 mA / cm 2 The overpotential of -122 mV was shown at a current density of 10 mA / cm 2 The overpotential was 137 mV at a current density of 1.
[0073] Comparative Example 2
[0074] Compared with Example 1, the difference is that the CeO2 / NF electrode is not subjected to sulfurization treatment, and the obtained electrode is a CeO2 / NF electrode.
[0075] The application method is the same as in Example 1, and the HER performance is -10 mA / cm 2 The overpotential of -208 mV was shown at a current density of 10 mA / cm 2 The overpotential was 343 mV at a current density of .
[0076] Comparative Example 3
[0077] Compared with Example 1, the difference is that the nickel foam electrode is not treated and the electrode is a NF electrode.
[0078] The application method is the same as in Example 1, and the HER performance is -10 mA / cm 2 The overpotential of -210 mV was shown at a current density of 10 mA / cm 2 It exhibits an overpotential of 487 mV at a current density of .
[0079] Comparative Example 4
[0080] Compared with Example 1, the difference is that annealing is only performed once, that is, annealing and sulfurization are performed in one step, and the area of 1cm 2 The CeO2 / NF precursor electrode and 1g thiourea were simultaneously transferred to a tubular furnace in a nitrogen atmosphere. The thiourea was placed upstream of the CeO2 / NF precursor electrode and the temperature was raised to 400°C at a heating rate of 1°C / min. Then, the temperature was annealed at 400°C for 2h. After the reaction, the catalyst obtained was a CeO2 / NiS catalyst.
[0081] The application method is the same as in Example 1, and the HER performance is -10 mA / cm 2 The overpotential of -156 mV was shown at a current density of 10 mA / cm 2 The overpotential is 207mV at a current density of Figure 1 It can be concluded from XRD that the CeO2 / NiS catalyst that has not undergone two annealing operations still contains some peaks of CeO2 precursor, resulting in poor performance of the catalyst.
Claims
1. A method for preparing a CeO2 / NiS heterostructure catalyst, characterized in that: The specific steps of the preparation method are as follows: (1) Pre-treating the surface of nickel foam; then dissolving cerium nitrate hexahydrate and urea in deionized water, dissolving and mixing evenly to obtain a mixed solution, transferring the mixed solution and nickel foam to a high-pressure reactor, heating and reacting, and after the reaction is completed, taking out the reactant, washing it with deionized water, and vacuum drying it to obtain a catalyst as a CeO2 / NF precursor; (2) annealing the CeO2 / NF precursor in a tubular furnace in a nitrogen atmosphere at a temperature of 300°C to 500°C to obtain a CeO2 / NF catalyst; (3) CeO2 / NF and thiourea are annealed in a tubular furnace in a nitrogen atmosphere at a temperature of 300°C to 500°C. Thiourea is placed upstream of the tubular furnace. The final catalyst obtained is a CeO2 / NiS heterostructure catalyst.
2. The method for preparing the CeO2 / NiS heterostructure catalyst according to claim 1, characterized in that: The molar ratio of cerium nitrate hexahydrate to urea in step (1) is 1:2-5.
3. The method for preparing the CeO2 / NiS heterostructure catalyst according to claim 1, characterized in that: In step (1), the molar ratio of cerium nitrate hexahydrate to urea is 2:
5.
4. The method for preparing the CeO2 / NiS heterostructure catalyst according to claim 1, characterized in that: In step (1), the ratio of nickel foam to cerium nitrate hexahydrate is 9 cm 2 : 1mmol~4mmol.
5. The method for preparing the CeO2 / NiS heterostructure catalyst according to claim 1, characterized in that: The hydrothermal reaction temperature in step (1) is 120° C. and the reaction time is 12 h.
6. The method for preparing the CeO2 / NiS heterostructure catalyst according to claim 1, characterized in that: The annealing time in step (2) is 2 h, and the heating rate is 1°C / min.
7. The method for preparing the CeO2 / NiS heterostructure catalyst according to claim 1, characterized in that: The annealing time in step (3) is 2 h, and the heating rate is 1°C / min.
8. The method for preparing the CeO2 / NiS heterostructure catalyst according to claim 1, characterized in that: The ratio of thiourea to CeO2 / NF in step (3) is 1g:1cm 2 .
9. An application of a CeO2 / NiS heterostructure catalyst prepared by the method according to any one of claims 1 to 8, characterized in that: The CeO2 / NiS heterostructure catalyst is used for electrocatalytic hydrogen evolution and / or electrocatalytic oxygen evolution in a three-electrode system under alkaline conditions and / or overall water splitting in a two-electrode system.
Citation Information
Patent Citations
Preparation method of transition metal oxide-nickel-based sulfide composite material through in-situ synthesis
CN109772367A
Nickel-sulfur composite hydrogen evolution electrode doped with foamed nickel load CeO2 and preparation method
CN107475743A
Nickel-iron bi-metal hydroxide@ cerium dioxide heterostructure nanosheet material and preparation method and application thereof
CN108447703A